Effect of Sonchus oleracea Extract on Some Virulence Factor of Klebsiella pneumonia Which Isolated from Urinary Tract Infection in Ramadi Hospital (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: The plant contains vitamin C, thiamin, riboflavin, and some citrus and saponins. Medicalbenefits of wrapping Its medicinal benefits are attributed to the similarity between it and chicory Tonic andregulator of sugar level in The blood is a diuretic, a strong purgative, lowers the level of cholesterol in theblood and combats scurvy, as it is anthelmintic Methodology: Klebsiella bacteria were isolated from patientssuffering from urinary tract infections in Ramadi General Hospital in selective media (Maconkey Agar),four concentrations of the aqueous and alcoholic extract were made 10%, 20%, 30 % and 40% to test theeffectiveness of the extracts in inhibiting growth and virulence factors for bacteria. Result: the effect of theaqueous and alcoholic extracts of the Sonchus oleracea extract on the production of the biofilm of Klebsiellabacteria, where it was observed that there were significant differences in the concentrations of the aqueousand alcoholic extract in reducing the production of the biofilm of the bacteria, and the best concentration ofthe aqueous and alcoholic extract was 40%, where the biofilm concentration was 31 compared to the restof the concentrations 3%, 20% and 10%, where its concentration reached .55, .64, and .74, respectively,and compared to the control, where its concentration was .98%. It was not noted that there were significantdifferences between the concentrations of plant extracts and aqueous and alcoholic extract in Reducingbiofilm yield. conclusion the results explain that this plant has many It is one of the effective compoundssuch as vitamin C, thiamin, riboflavin, and some citrus and saponins. That destroy the cell wall and thusreduce the production of the biofilm and that these compounds increase by increasing the concentration ofplant extracts, and this explains the effect of the high concentration in reducing the production of the biofilm.
Keywords: of Sonchus oleracea extract, virulence factor of klebsiella pneumonia